2010
DOI: 10.1177/0042085909355763
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning: Academic and Social Performance of African Immigrant Students in an American High School

Abstract: Student achievement data in schools are often analyzed in terms of ethnic and racial parameters. Such data categorize African immigrant students as African Americans, thus creating an impression of homogeneity within the African American racial group. Given that these immigrant students relocate to the United States with cultural backgrounds that shape their views on educational opportunities, their school experiences render a unique perspective on the dynamics of schooling in the United States. Students enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…For example, Mullins (2010) found that English-speaking Caribbean and Africanborn students were more likely to go to college than non-English-speaking peers in their ethnic groups in Toronto. Njue and Retish (2010) same trend in their study of African immigrant students at an American high school. Some Canadian researchers further pointed out that refugee youth with limited literacy skills in their first language and/or English are very disadvantaged and challenged, causing high drop-out rates (Derwing, Decorby, Ichikawa, & Jamieson, 1999;Watt & Roessingh, 1994, 2001) and gang involvement (Ngo, Calhoun, Worthington, Pyrch, & Este, 2017;Rossiter & Rossiter, 2009).…”
Section: Academic Adjustment and Contributing Factorssupporting
confidence: 55%
See 1 more Smart Citation
“…For example, Mullins (2010) found that English-speaking Caribbean and Africanborn students were more likely to go to college than non-English-speaking peers in their ethnic groups in Toronto. Njue and Retish (2010) same trend in their study of African immigrant students at an American high school. Some Canadian researchers further pointed out that refugee youth with limited literacy skills in their first language and/or English are very disadvantaged and challenged, causing high drop-out rates (Derwing, Decorby, Ichikawa, & Jamieson, 1999;Watt & Roessingh, 1994, 2001) and gang involvement (Ngo, Calhoun, Worthington, Pyrch, & Este, 2017;Rossiter & Rossiter, 2009).…”
Section: Academic Adjustment and Contributing Factorssupporting
confidence: 55%
“…For example, students from cultures that highly value formal education, especially East and Southeast Asian countries with a Confucian educational heritage, tend to perform well academically (Chow, 2000;Costigan, Su, & Hua, 2010;Garnett, 2010;Mullins, 2010;Toohey & Derwing, 2008;Zhou & Bankston, 1998). The American high school students of African origin in Njue and Retish's (2010) study had a "deep-seated desire to acquire education" (p. 366) because they came from environments where opportunities to obtain education were scarce and going to school was equated with higher social status.…”
Section: Academic Adjustment and Contributing Factorsmentioning
confidence: 99%
“…21, 758) While it would be decades before its full impact would be felt, the legislation helped to usher significant changes to the ethno-racial landscape of the United States. Due to the 1965 legislation, the percentage of immigrants admitted under the family unification provision increased from around 14% in the mid-1960s to 70% by 1980 (Njue & Retish, 2010). As reflected in Table 4.1, in 1970 the US foreign-born population represented less than 5% of the total population, its lowest level in the twentieth century.…”
Section: Changing Demographic Makeup Of the Us Immigrant Populationmentioning
confidence: 99%
“…An examination of transcripts (Albertini, 2004) revealed that mean cumulative middle school GPA for immigrant Black middle school students from the Caribbean varied from 1.88 to 1.81 on a four-point scale. Research using standardized test scores as outcome variables (Njue & Retish, 2010) revealed that immigrant Black middle school students from Africa outperformed their non-immigrant Black peers in math skills (29% and 25% pass rate, respectively), but in reading the pattern was reversed (39% and 47% pass rate for immigrant and non-immigrant students, respectively). Taken together, findings demonstrate variability in participation and persistence in higher education despite similar constraints in academic preparation for Black students.…”
Section: Getting Ready For Collegementioning
confidence: 99%